2015
DOI: 10.1038/srep14188
|View full text |Cite
|
Sign up to set email alerts
|

High diversity and rapid diversification in the head louse, Pediculus humanus (Pediculidae: Phthiraptera)

Abstract: The study analyzes sequence variation of two mitochondrial genes (COI, cytb) in Pediculus humanus from three countries (Egypt, Pakistan, South Africa) that have received little prior attention, and integrates these results with prior data. Analysis indicates a maximum K2P distance of 10.3% among 960 COI sequences and 13.8% among 479 cytb sequences. Three analytical methods (BIN, PTP, ABGD) reveal five concordant OTUs for COI and cytb. Neighbor-Joining analysis of the COI sequences confirm five clusters; three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(106 citation statements)
references
References 62 publications
(82 reference statements)
6
99
0
1
Order By: Relevance
“…Haplogroup A is the most common, and possesses a global distribution, including both head and body lice [1, 2, 6, 8, 9]. Clade B comprises only head lice, is confined to the New Word, Europe, Australia and was recently reported in North and South Africa [2, 6, 10, 11]. Clade C includes only head lice and is mainly found in Africa and Asia [2, 5, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplogroup A is the most common, and possesses a global distribution, including both head and body lice [1, 2, 6, 8, 9]. Clade B comprises only head lice, is confined to the New Word, Europe, Australia and was recently reported in North and South Africa [2, 6, 10, 11]. Clade C includes only head lice and is mainly found in Africa and Asia [2, 5, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research suggested that the known lice clades evolved on different lineages of Homo , similarly to those which are known to have existed 2.3 to 0.03 million years ago (MYA) [1, 11], and accordingly their geographic distribution may provide information regarding the evolutionary history of the lice as well as their human hosts [1, 2, 22]. Clade A lice are most likely to have emerged in Africa and to have evolved on the host linage that led to anatomically modern humans ( Homo sapiens ), showing the signs of a recent demographic expansion out of Africa about 100,000 years ago, first to Eurasia and subsequently to Europe, Asia, and the New World [1, 5, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the 4.5 million animal records on BOLD has been assigned to a BIN, a Barcode Index Number (Ratnasingham and Hebert 2013), generating 452 000 BINs, predominantly insects (315 000) (accessed 21 April 2016). Because BINs show strong congruence with species designated through past morphological study (Pentinsaari et al 2014;Zahiri et al 2014;Mutanen et al 2015), they can be viewed as species proxies (Telfer et al 2015) to facilitate the assessment of large-scale biodiversity patterns (Blagoev et al 2016) and the detection of cryptic species complexes (Kekkonen and Hebert 2014;Ashfaq et al 2015). The use of barcode data to identify species (Rakauskas and Basilova 2013) as opposed to BINs requires the species in question be represented in the barcode reference library (Ekrem et al 2007).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Lineages showing sequence divergence, often termed molecular operational taxonomic units (MOTUs) (Blaxter et al 2005), have been discriminated by analyzing sequence variation using distance analysis (Schloss and Handelsman 2005), neighborjoining clustering (Saitou and Nei 1987), phylogenetic trees (Zhang et al 2013), Bayesian inference (Yang and Rannala 1997), coalescence-based approach (Pons et al 2006;Fujisawa and Barraclough 2013), barcode-gap analysis (Puillandre et al 2012), and BINs (Ratnasingham and Hebert 2013). However, there is a growing trend to integrate multiple methods (Ashfaq et al 2015;Kekkonen et al 2015;Blagoev et al 2016) and multiple markers (Jörger et al 2012;Mrinalini et al 2015) to assess MOTU diversity. The results from such analyses have frequently been helpful in resolving taxonomic problems and in estimating species richness and abundance (Unterseher et al 2011;Mutanen et al 2013;Stahlhut et al 2013).…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…However, the implementation of the Barcode Index Number (BIN) system [12] as a proxy for species [13] is allowing DNA barcoding to support biodiversity assessment [14], providing the opportunity to accelerate biotic inventories [1520]. As a consequence, BINs have already been used to examine animal biodiversity [21,22] at regional [23] and global [24] scales.…”
Section: Introductionmentioning
confidence: 99%